The Economics of Managerial Decisions, Global Edition - Blair, Roger (Pearson International Content, 2019)
For courses in managerial economics. Teaching students managerial economics through real examples, real businesses, with real-life situations The Economics of Managerial Decisions teaches students how to make business decisions by blending the qualitative and quantitative aspects of the course. Using examples from different sectors of the economy, the authors present real examples, such as Pizza Hut, to teach the concepts of production and cost, and KV Pharmaceuticals, to talk about monopoly — helping students see how theory is applied in different contexts. The full text downloaded to your computer With eBooks you can: search for key concepts, words and phrases make highlights and notes as you study share your notes with friends eBooks are downloaded to your computer and accessible either offline through the Bookshelf (available as a free download), available online and also via the iPad and Android apps. Upon purchase, you'll gain instant access to this eBook. Time limit The eBooks products do not have an expiry date. You will continue to access your digital ebook products whilst you have your Bookshelf installed.